The effect of kinesiotape on function, pain, and motoneuronal excitability in healthy people and people with Achilles tendinopathy - Firth,BL; Dingley,P; Davies,ER; Lewis,JS; Alexander,CM (Clin J Sport Med., 2010)
OBJECTIVE: To investigate the effect of kinesiotape on hop distance, pain, and motoneuronal excitability in healthy people and people with Achilles tendinopathy (AT). DESIGN: Within-subject design. SETTING: An academic health science center, which is an acute London National Health Service trust. PARTICIPANTS: With ethical approval and informed consent, a convenience sample of 26 healthy people and 29 people with AT were recruited. Seven participants were lost after functional testing, leaving 24 participants in each group. INTERVENTIONS: Kinesiotape applied over the Achilles tendon. MAIN OUTCOME MEASURES: The single-leg hop test and visual analog scale were measured with and without the tape. Using the Hoffman (H) reflex, change in motoneuronal excitability of calf muscles was measured before tape application, with the tape on and after its removal. RESULTS: There were no changes to hop distance when tape was applied (P = 0.55). Additionally, there were no changes to pain (P = 0.74). The H reflex amplitude of soleus and gastrocnemius increased in the healthy group after its removal (P = 0.01 and P = 0.03, respectively), whereas the H reflex remained unchanged in people with AT (P = 0.43 and 0.16, respectively). CONCLUSIONS: Calf muscles were facilitated by kinesiotape in healthy participants. Despite this, there was no change to hop distance. Kinesiotape had no effect on hop distance, pain, or motoneuronal excitability in people with AT. These results do not support the use of kinesiotape applied in this way for this condition